Use of special technical means (polygraph) on personnel recruitment in corporate structures - A. Yu. Tsygankov; A. A. Kravchuk (Вестник университета)
The article studies some aspects of specialized polygraph device application in the process of personnel recruitment in corporate structures. The authors cite the sociological surveys results that reflect the attitude of employers and employees towards polygraph checks at the stage of their employment. The methods and spheres of polygraph application for professional-psychological selection have been analyzed. The special psychophysiological research procedure with the use of the polygraph has been described, including recommendations on the questions formulation to obtain reliable results. The legislation of the Russian Federation regulating the conduct of such research has also been considered. The authors concluded that the use of the polygraph device is a relevant and promising tool, which is increasingly used in the personnel recruitment in corporate structures, as evidenced by the sociological surveys results. However, the research peculiarity on the polygraph tests prospects in personnel recruitment is currently complicated by the lack of open data from the companies themselves, since such data constitute commercial secrets and are not subject to public disclosure in accordance with the Federal Law “On Trade Secrets”.